2017
DOI: 10.1002/widm.1237
|View full text |Cite
|
Sign up to set email alerts
|

A survey of evaluation methods for personal route and destination prediction from mobility traces

Abstract: Personal mobility data can nowadays be easily collected by personal mobile phones and used for analytical modeling. To assist in such an analysis, a variety of computational approaches have been developed. The goal is to extract mobility patterns in order to provide traveling assistance, information, recommendations or on‐demand services. While various computational techniques are being developed, research literature on destination and route prediction lacks consistency in evaluation methods for such approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the choice of risk estimated method along with the motion model are the two major components for motion prediction and risk estimation for intelligent automobiles. Similarly, a study analyzed the different computational approaches developed for personal mobility [ 28 ]. An experimental analysis was performed on the unpublished mobility data of 15 users in the Helsinki metropolitan area.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the choice of risk estimated method along with the motion model are the two major components for motion prediction and risk estimation for intelligent automobiles. Similarly, a study analyzed the different computational approaches developed for personal mobility [ 28 ]. An experimental analysis was performed on the unpublished mobility data of 15 users in the Helsinki metropolitan area.…”
Section: Related Workmentioning
confidence: 99%
“…With this purpose, these models are described by equations which take into account physical laws of motion. On the other hand, some models are inspired by real mobility traces in order to model real-life movements (Stegmann et al 2018;Ibadah et al 2018a). Notwithstanding, in all cases, the major challenge is how to achieve the best possible performance for wireless Communications in the presence of frequent mobility (Batabyal and Bhaumik 2015).…”
Section: Related Workmentioning
confidence: 99%